Ethical Education in Plutarch : Moralising Agents and Contexts. - Xenophontos, Sophia (Beiträge zur Altertumskunde., 2016)
Bringing together a wide range of texts from both the Parallel Lives and the Moralia, this study puts the moralising agents that Plutarch considers important for ethical development at the heart of its interpretation. Ethical education in Plutarch becomes a distinctive manifestation of paideia vis-à-vis the intellectual trends of the Imperial period, especially in contexts of cultural identity and power.